South-Indian horizons : felicitaion volume for Francois Gros on the occasion of his 70th birthday - Gros, Franc̨ois; Chevillard, Jean-Luc; Wilden, Eva.; Murugaiyan, A., edt ([Pondicherry] : Institut Franc̨ais De Pondichery, [and] École Franc̨aise D'Extreme-Orient, 2004)
Zbornik radova, uglavno posvećenih tamilskom jeziku i književnosti
Str. xxvi-xxix: bibliografija
Sadrži dijelove teksta na tamilskom
Keywords: tamilska filologija -- tamilski jezik -- tamilska književnost -- zbornik radova